How Do Dental Clinicians Obtain Up-To-Date Patient Medical Histories? Modeling Strengths, Drawbacks, and Proposals for Improvements - Li, Shuning; Rajapuri, Anushri Singh; Felix Gomez, Grace Gomez; Schleyer, Titus; Mendonca, Eneida A.; Thyvalikakath, Thankam P. (Frontiers in Digital Health, 2022)
Background: Access to up-to-date patient medical history is essential for dental clinicians (DCs) to avoid potential harm to patients and to improve dental treatment outcomes. In this study, we built conceptual models on the DCs’ current approaches to gathering patient medical information. We also proposed an alternative approach for DCs to access patient medical history via a regional health information exchange (HIE) platform. Methods: There are three phases in this study. In Phase 1, we retrieved peer-reviewed PubMed indexed manuscripts published between January 2013 and November 2020 and extracted modeling related data from selected manuscripts. In Phase 2, we built models for the current approaches by using the Integrated DEFinition Method 0 function modeling method (IDEF0), the Unified Modeling Language (UML) Use Case Diagram, and Business Process Model and Notation (BPMN) methods. In Phase 3, we created three conceptual models for the HIE approach. Results: From the 47 manuscripts identified, three themes emerged: 1) medical consult process following patient-reported medical history, 2) integrated electronic dental record-electronic health record (EDR-EHR), and 3) HIE. Three models were built for each of the three themes. The use case diagrams described the actions of the dental patients, DCs, medical providers and the use of information systems (EDR-EHR/HIE). The IDEF0 models presented the major functions involved. The BPMN models depicted the detailed steps of the process and showed how the patient’s medical history information flowed through different steps. The strengths and weaknesses revealed by the models of the three approaches were also compared. Conclusions: We successfully modeled the DCs’ current approaches of accessing patient medical history and designed an HIE approach that addressed the current approaches’ weaknesses as well as leveraged their strengths. Organizational management and end-users can use this information to decide the optimum approach to integrate dental and medical care. The illustrated models are comprehensive and can also be adopted by EHR and EDR vendors to develop a connection between dental systems and HIEs.